HUBUNGAN LINGKUNGAN SEKOLAH DENGAN MOTIVASI BELAJAR PADA MATA PELAJARAN DASAR KOMPETENSI KEJURUAN JASA BOGA - Lestari, Ayu Puji; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims to determine the relationship of the school environment with learning motivation in basic subjects of vocational competency skills program Hospitality SMK Padang 9. This type of research is a correlational study. The population in this study were students of class X Catering competency skills, the sample in this study amounted to 62 people with a random sampling technique. The data analysis technique used is the correlation product moment correlation formula. The results showed that the school environment SMK Padang including 9 in the category Good Enough Learning and motivation of students in basic subjects of vocational competency skills program vocational 9 SMK Padang included in the category of Good Enough. The relationship between school environment variables (X) with the motivation to learn basic vocational competencies (Y), has a significant and positive relationship with a correlation of 0.436, the significance of the correlation coefficient test results tarithmetic > ttable (3.756 and 2.001> 1.9949. Â Kata kunci: lingkungan sekolah, motivasi belajar, dasar kompetensi kejuruan